Arctic Ocean Freshwater in CMIP6 Ensembles: Declining Sea Ice, Increasing Ocean Storage, and Export. Issue 4 (12th April 2021) - Zanowski, Hannah; Jahn, Alexandra; Holland, Marika M.
Abstract: The Arctic has undergone dramatic changes in sea ice cover and the hydrologic cycle, both of which strongly impact the freshwater storage in, and export from, the Arctic Ocean. Here we analyze Arctic freshwater storage and fluxes in seven climate models from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and assess their performance over the historical period (1980–2000) and in two future emissions scenarios, SSP1‐2.6 and SSP5‐8.5. Similar to CMIP5, substantial differences exist between the models' Arctic mean states and the magnitude of their 21st century storage and flux changes. In the historical simulation, most models disagree with observations over 1980–2000. In both future scenarios, the models show an increase in liquid freshwater storage and a reduction in solid storage and fluxes through the major Arctic gateways (Bering Strait, Fram Strait, Davis Strait, and the Barents Sea Opening) that is typically larger for SSP5‐8.5 than SSP1‐2.6. The liquid fluxes are driven by both volume and salinity changes, with models exhibiting a change in sign (relative to 1980–2000) of the freshwater flux through the Barents Sea Opening by mid‐century, little change in the Bering Strait flux, and increased export from the remaining straits by the end of the 21st century. In the straits west of Greenland (Nares, Barrow, and Davis straits), the models disagree on the behavior of the liquid freshwater export in the early‐to‐mid 21st century due to differences in the magnitude and timing of a simulated decrease in the volume flux. Plain Language Summary: The Arctic Ocean has changed dramatically due to melting sea ice and increasing river water input and rain‐ and snowfall. Keeping track of these sources of freshwater helps us understand how the Arctic Ocean is changing and how it will change in the future. In this study, we use several state‐of‐the‐art climate models to understand these freshwater changes by calculating the amount of freshwater stored in, and transported in and out of, the Arctic Ocean. We first compare the models' freshwater values to observations and then determine how these values have changed at the end of the 21st century. We find that most models do not agree well with observations, and large differences in the size of the freshwater storage and transport also exist between them. Despite these differences, all models show that freshwater stored in and transported by sea ice decreases strongly by the end of the 21st century, while freshwater stored in the Arctic Ocean increases as well as freshwater transported out of the Arctic Ocean in most places. These changes indicate that by the end of this century the Arctic Ocean will be very different than it is today. Key Points: Historical Arctic freshwater storage and fluxes vary widely across a subset of CMIP6 models and few are consistently close to observations Projections show declining solid and increasing liquid freshwater storage and fluxes in agreement with previous CMIP studies Large uncertainty exists in projections of liquid freshwater fluxes west of Greenland due to model differences in simulated velocities